RISK FACTORS OF PNEUMONIA IN INFANTS AT PUBLIC HEALTH CENTER OF KAMONJI - Frini, Merlinda; Rahman, Nurdin; Herman, Herman (Tadulako University, 2018)
Background & Objective: Pneumonia is one cause of leanding cause of death in children wordwide, as it is one of the most serious respiratory infections that mostly affect children and high case makes pneumonia the second leading cause of death after diarrhea on children. The number of cases of pneumonia at Kamonji Public Health Center Palu City in 2015 amounted to 495 cases and in 2016 increased to 536 cases. The objective of this research is to find out the risk factors of Pneumonia at the working area of Kamonji Public Health Center Palu. Material and Method: The research type was analytic observational with case control design. Sampling used were accidental sampling and purposive sampling with ratio 1: 2 where case sample counted 80 people and control sample counted 160 people. The data collected through questionnaires by conducting interviews to respondents and performing direct measurements. Result: The results of the research with OR analysis show that nutritional status (OR = 3.857; 95% CI 2.182-6.818), exclusive breasfeeding (OR = 3.039; 95% CI 1.652-5.592) and vitamin A intake (OR = 2,105; 95% CI 1.209 -3,665), is a risk factor of pneumonia occurrence. Gender (OR = 1,357; 95% CI 0,787-2,339) there is no significant relationship. Conclusion: Nutritional status, exclusive breastfeeding and intake of vitamin A are risk factors of pneumonia in infants in the Kamonji Public Health Center Palu City